Consent: from generation to co-production - Fernandez, Artchil (Social Sciences and Development Review, 2024)
The concept of consent and its origin is a topic of intense debate within academia. This paper contributes to the discussion by examining two main perspectives on consent. One viewpoint argues that consent is manufactured or produced, particularly by the ruling class, known as the Marxist perspective on consent. This perspective is supported by the ideas of three influential Marxist thinkers – Antonio Gramsci, Michael Burawoy, and Louis Althusser. The other perspective on consent comes from relational sociology, which suggests that consent is a collaborative effort between the parties involved. This paper delves into the works of three sociologists – Charles Tilly, Pierre Bourdieu, and Nick Crossley – associated with the relational approach in sociology to explore consent as a collaborative process. It presents two contrasting viewpoints on the concept of consent and how it is originated. The paper argues that consent can be not only manufactured but also co-created by social actors. Moreover, it introduces relational sociology by applying it to analyze consent and its creation, generation, and co-production within society. Though the relational approach in sociology is relatively recent, its roots can be traced back to the early days of the discipline in the Durkheim-Tarde debate and the contributions of Georg Simmel. This paper provides an overview of relational sociology, using it as a framework to examine the concept of consent, particularly its generation.
Keywords: consent generation; consent co-production; hegemony; relational sociology